Piezosurgery: A new and safe technique for distraction osteogenesis in Pierre Robin sequence review of the literature and case report - Galié, Manlio (Int J Surg Case Rep, 2014)
INTRODUCTION: Pierre Robin sequence (PRS) is characterized by microgenia and retrognathia. Cleft palate and glossoptosis are frequently associated with airway obstruction and difficulty in swallowing. Distraction osteogenesis with micro-distractors has recently been considered as a surgical option during the neonatal age. CASE PRESENTATION: A 6-week-old female with PRS underwent mandibular lengthening in neonatal age. Mandibular osteotomies were performed with the piezoelectric scalpel. DISCUSSION: Piezosurgery represents an innovative technique as it offers the maxillofacial surgeon the opportunity to make precise bone cuts without damaging the soft tissue, minimizing the invasiveness of the surgical procedure, and the opportunity of working in a field which is almost totally blood free. CONCLUSION: The use of a piezoelectric device to perform this kind of surgery provides clinical and surgical results which would be difficult with traditional instruments, not only for the patient’s benefit but also for the surgeon’s. Preservation of the original bony structure, especially of the cancellous bone, will benefit the bone healing process due to its high estrogenic potential.